The privatization process in Central Europe : economic environment, legal and ownership structure, institutions for state regulation, overview of privatization programs, initial transformation of enterprises - Frydman, Roman, 1948- (CEU privatization reports ;, 1993)
"For the first time comprehensive comparative information on five Central European countries has been collected by teams of researchers from within the region and the West." "Following an introduction to the economic environment in each country, this volume provides an overview of the privatization process in Central Europe, including an account of the legal framework of economic activity, the present forms of ownership, institutions for state regulation, an overview of privatization programs, and the initial transformation of enterprises." "The strength of this volume lies in the authors' unique access to hitherto unavailable information and their ability to present a vast amount of material in an easily accessible format." "Policy makers and business people will find it easy to extract the facts and figures they require, while the wealth of information on this subject will provide a strong foundation for future research."--Jacket.